Factors Affecting Financial Performance of Nepalese Life Insurance Companies - Srivastava, Anamika; Sah, Khushbu (Campion Journal of Multidisciplinary Research and Explorer, 2025)
This research examines the determinants affecting the financial performance of life insurance companies in Nepal, with a focus on key metrics such as Return on Assets (ROA) and Return on Equity (ROE). The study employs secondary data from six Nepalese life insurance companies, using descriptive statistics, correlation analysis, and multiple regression techniques to evaluate the influence of factors such as company size, company age, liquidity, inflation, and premium growth. The findings reveal that company size, company age and liquidity have a negative impact on ROA, whereas premium growth and inflation exhibit positive effects. In contrast, inflation, company age and company size negatively impact ROE, while premium growth and liquidity positively influence ROE. Among the variables analyzed, company size emerges as a significant predictor of financial performance. The results underscore the importance of both internal factors, such as premium growth and company-specific attributes, and external conditions like inflation, in shaping the financial outcomes of Nepalese life insurance companies. The study highlights the necessity for effective financial and operational management strategies to achieve sustainable performance.